Self-Compassion: Evaluation of a Psychoeducational Website. Issue 2 (15th June 2016) - Talbot, France; Thériault, Judith; French, Douglas J.
Abstract : Background: Low levels of self-compassion are associated with a number of mental health problems. Recent findings suggest that self-compassion can be significantly increased through traditional therapist led interventions such as Mindful Self-Compassion (MSC).Aims: The goal of this study was to assess the impact of a psychoeducational website modeled on MSC on measured levels of self-compassion and two related constructs: shame and rumination.Method: Participants ( N = 9) were recruited from a pool of university students and employees. Single case AB protocols were used.Results: Analyses using the Critical Difference statistic revealed significant improvement in self-compassion and shame for the majority of participants, but limited changes in rumination.Conclusions: These preliminary findings suggest that self-compassion may be enhanced through the use of a psychoeducational website. It may be worthwhile to develop a structured internet-based treatment course for individuals who would not otherwise access traditional psychological services.